Ministry Of Finance Decree No. 124 of the Year 2017 = وزارة المالية قرار رقم 124 لسنة 2017 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
Article 1: In applying the provisions of tax on capital profits resulting from transacting in securities registered in the Stock Exchange, the phrase: "the central depository and registry company and the depository banks licensed to practice the activity as the case may be or the entity carrying out the transaction" stated in articles nos. (52-Bis-3) and (77-Bis) of the executive regulations of law no. 91 of the year 2005 shall be replaced with the following phrase: "the entity to be determined by a decree of the minister of Finance".